An adolescent girl with obstructive uropathy requiring nephro-ureterectomy was subsequently diagnosed with renal tuberculosis: case report. (3rd April 2021) - Kaba, Özge; Kara, Manolya; Bayramoğlu, Zuhal; Çalışkan, Emine; Çetin, Bilal; Karimov, Elnur; Özkuvancı, Ünsal; Özlük, Yasemin; Hançerli Torun, Selda; Yürük Yıldırım, Zeynep Nagehan; Ziylan, Hasan Orhan; Somer, Ayper
ABSTRACT: A 15-year-old girl was followed up for 2 years in a district hospital for management of vesicoureteral reflux and, subsequently, hydronephrosis of both kidneys and required bilateral ureteroneocystostomy. Despite surgery, there was continuous progression of the left hydronephrosis. Referral to a tertiary hospital because of continued sterile pyuria prompted investigation for tuberculosis (TB): she was diagnosed with bilateral pulmonary TB and urine culture confirmed Mycobacterium tuberculosis . Despite tuberculous chemotherapy and dexamethasone, she required a left nephrectomy. Histology demonstrated necrotising granulomatous pyelonephritis. She remains well with normal function of the right kidney. Despite the rarity, chronic urinary tract disorders should always prompt investigation for tuberculosis.